Membangun Industri Konstruksi Indonesia Menjadi Kelas Dunia - Hadihardaja, Joetata (Department of Civil Engineering, Diponegoro University, 2005)
Multi dimension crisis that has been happening since 1997 in Indonesia, generates remarkable economics impact and also has an effect on the world of construction industry company. To develop world-class construction industry, it is needed entirely evaluation, not just in the industrial company itself, but also in related parties. Based on the evaluation, recommendations such as the importance of reconstruction certification and of revitality to increase construction industry performance, will be gathered. Contribution of human resources is depending on worker ability including achievement and potential ability. Construction industry can apply Quality of Work Life (QWL) systematically, so workers will feel be treated, be trusted, be respected and be participated as part of company that expands become a world-class company. Keywords: Construction industry, problems, certification, world-class industrial companyPermalink: http://ejournal.undip.ac.id/index.php/mkts/article/view/3904[How to cite: Hadihardaja, J., 2005, Membangun Industri Konstruksi Indonesia Menjadi Kelas Dunia, Jurnal Media Komunikasi Teknik Sipil, Volume 13, Nomor 2, pp. 11-19]